Evaluation of the reactor building environmental conditions under a LOCA for the decommissioning Chinshan plant. (15th June 2021) - Chen, Yen-Shu; Huang, Li-Ying
Highlights: Two Chinshan BWR units are under decommissioning. Reactor, cavity and spent fuel pool are connected in the mode 5 + condition. Thermal conditions of the reactor building should be quantitatively analyzed. Accident analysis is performed using GOTHIC. The reactor building is regarded as a mild environment in the 6 days following the accident. Abstract: Both units of the Chinshan plant have been approved for decommissioning. However, fuel assemblies cannot be discharged from the reactor core because the spent fuel pool (SFP) is almost full. Currently, the reactor remains open and connected to the SFP. This configuration would persist for years. Considering this, the nuclear regulatory authority requires the safety-grade instruments in the reactor building to remain operable under accident conditions. However, a loss of coolant accident in this configuration was not analyzed before. In this study, thermal analysis using GOTHIC is performed to evaluate the environmental conditions in the reactor building. The reactor, SFP, primary containment and reactor building are included. The results show that the reactor building temperature remains below 48.9 °C during 6 days following the accident. Thus, recovering any cooling function in 6 days following the accident is suggested. This ensures that the reactor building space is in a mild environment.